2008
DOI: 10.1038/labinvest.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Potential utility of xenobiotic mitogens in the context of liver regeneration in the elderly and living-related transplantation

Abstract: Although liver regeneration occurring after partial hepatectomy (PH) is greatly reduced in aged mice, liver hyperplasia induced by xenobiotic mitogens was found to be age independent. Here, we investigated the potential utility of mitogens in stimulating liver regeneration in old mice subjected to two-third PH. Although virtually no hepatocytes entered S phase 48 h after PH, pretreatment (2 h prior to surgery) with 1,4-bis(2-(3,5-dichloropyridyloxy)benzene (TCPOBOP), a ligand of constitutive androstane recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, we investigated whether the enhanced YAP expression observed in the liver of old mice is the result of mechanisms that Bsense^the decreased liver mass and signal a proliferative response in an attempt to re-establish the original organ size. To better understand whether liver size dictates YAP expression, we evaluated its protein content in young mice subjected to surgery after induction of hepatomegaly by treatment with the hepatomitogen TCPOBOP (Columbano et al 2008). Animals were sacrificed 72 h after PH, since under this condition, hepatic mass reaches the values of the liver of intact animals within 3 days (Columbano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we investigated whether the enhanced YAP expression observed in the liver of old mice is the result of mechanisms that Bsense^the decreased liver mass and signal a proliferative response in an attempt to re-establish the original organ size. To better understand whether liver size dictates YAP expression, we evaluated its protein content in young mice subjected to surgery after induction of hepatomegaly by treatment with the hepatomitogen TCPOBOP (Columbano et al 2008). Animals were sacrificed 72 h after PH, since under this condition, hepatic mass reaches the values of the liver of intact animals within 3 days (Columbano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand whether liver size dictates YAP expression, we evaluated its protein content in young mice subjected to surgery after induction of hepatomegaly by treatment with the hepatomitogen TCPOBOP (Columbano et al 2008). Animals were sacrificed 72 h after PH, since under this condition, hepatic mass reaches the values of the liver of intact animals within 3 days (Columbano et al 2008). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose we chose to induce liver fibrosis using two standard protocols. The upregulation of CYP2b10, a target gene of TCPOBOP’s receptor, CAR (Columbano et al. 2008) indicated that there was an intact signal transduction pathway, although the induction was less intense in cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…2006). The decreased regenerative response of liver in aged mice was also explained by increased p27 expression (Columbano et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation